Need analysis for innovation in integrated learning models for micro-teaching course: Explanatory sequential design - Blegur, Jusuf; Ma'mun, Amung; Berliana, Berliana; Mahendra, Agus; Layao, Michelle Mordeno (Universitas Negeri Yogyakarta, 2024)
One of the keys to successful learning model development is conducting a comprehensive needs analysis on actual performance, desired performance, and causes of performance gaps. This research aims to analyze student performance needs so that they can become a credible basis for consideration when designing the syntax of learning experiences for integrated learning models for micro-teaching courses. Researchers used an explanatory sequential design when completing the study, so quantitative research became the main focus for data collection and analysis, which was emphasized by qualitative studies. There were 107 research respondents, namely 75 students, two lecturers, and 30 physical education teachers. Data on actual performance, desired performance, and causes of performance gaps on the variables of teaching skills, analytical thinking skills, academic integrity, and transformational leadership were collected using 12 statements. Qualitative data was collected using semi-structured interviews. Data were analyzed descriptively and with Kruskal-Wallis to test differences in actual performance and desired performance of the three groups of respondents. Meanwhile, for qualitative data, researchers used thematic analysis. The results of the Kruskal-Wallis test prove that there are no significant differences between the three groups of respondents in actual performance (0.365> 0.05) or desired performance (0.758> 0.05). Students, lecturers, and teachers agree that teaching skills, analytical thinking skills, academic integrity, and transformational leadership are important requirements in developing integrated learning models. Meanwhile, the causes of performance gaps are not limited to lack of training experience, lack of opportunity to analyze problems and make decisions, lack of role models, or lack of support from lecturers and colleagues in lectures. Thus, in developing the model, the performance tasks designed must be able to overcome this performance gap by increasing students' experience in operational and clinical exercises during lectures